Challenges and adaptations in teaching mathematics during the pandemic: a qualitative analysis of teaching experiences with ICTs in Costa Rica: Desafíos y adaptaciones en la enseñanza de las matemáticas durante la pandemia: un análisis cualitativo de experiencias docentes con TIC en Costa Rica - Gutiérrez-Ruiz, Grettel (2026)
This study reports the findings of research exploring the experiences and challenges faced by secondary school mathematics teachers in Costa Rica when rapidly integrating Information and Communication Technologies (ICT) into their teaching due to the COVID-19 pandemic. This qualitative study involved 12 teachers with over 10 years of experience from various provinces, participating in virtual focus groups. Data analysis using MAXQDA software revealed key challenges, including work-related stress, connectivity issues, lack of institutional support, and concerns about student learning in virtual environments. Despite efforts by the Ministry of Public Education and other institutions to enhance ICT training for teachers, these initiatives were perceived as insufficient and delayed. The study concludes that continuous professional development and equitable access to technological resources are essential for the effective integration of ICT in mathematics education.